2014
DOI: 10.1111/apt.12899
|View full text |Cite
|
Sign up to set email alerts
|

Randomised clinical trial: the long‐term safety and tolerability of naloxegol in patients with pain and opioid‐induced constipation

Abstract: SUMMARY BackgroundOpioid-induced constipation (OIC) is a common adverse effect of opioid therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
141
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(154 citation statements)
references
References 14 publications
4
141
0
9
Order By: Relevance
“…Serious adverse events did not occur in any of the randomized controlled trials Webster et al 2014]. QT/QTc interval prolongation was not observed when 150 mg of naloxegol was given to healthy men [Gottfridsson et al 2013].…”
Section: Naloxegolmentioning
confidence: 86%
“…Serious adverse events did not occur in any of the randomized controlled trials Webster et al 2014]. QT/QTc interval prolongation was not observed when 150 mg of naloxegol was given to healthy men [Gottfridsson et al 2013].…”
Section: Naloxegolmentioning
confidence: 86%
“…Vrlo uporno neželjeno dejstvo opioidne terapije, uprkos dobrom kupiranju bola, značajno remeti kvalitet života pacijenata. Ovo je navelo farmaceutske kuće da razmišljaju o uvođe-nju leka koji bi kupirao gastrointestinalna neželje-na dejstva opioida 41 . Biohemijskom modifikacijom α-naloxola došlo se do oralne formulacije leka veće molekulske mase, koji ostvaruje lokalni efekat na μ2-opioidnim receptorima.…”
Section: α-Naloxolunclassified
“…The authors concluded that treatment with naloxegol, as compared with placebo, resulted in a significantly higher rate of treatment response, without reducing opioidmediated analgesia [35 && ]. The long-term safety of naloxegol was addressed in a 52-week, multicenter, open-label, randomized, parallel-group phase 3 study [47] in patients with noncancer pain and OIC. Patients were randomized 2 : 1 to receive oral naloxegol 25 mg/day or usual care (usual care; investigator-chosen laxative regimen) treatment for OIC.…”
Section: Key Pointsmentioning
confidence: 99%
“…Treatment-emergent adverse events occurring more frequently for naloxegol versus usual care were abdominal pain (17.8 versus 3.3%), diarrhea (12.9 versus 5.9%), nausea (9.4 versus 4.1%), headache (9.0 versus 4.8%), flatulence (6.9 versus 1.1%) and upper abdominal pain (5.1 versus 1.1%). Most naloxegol-emergent gastrointestinal adverse events occurred early, resolving during or after naloxegol discontinuation and were mild or moderate in severity [47].…”
Section: Key Pointsmentioning
confidence: 99%